Single Receiver Heighting Using The Active Stations Of The National GPS Network Of Great Britain - Penna, Nigel; Bingley, R.; Dodson, A. (Commonwealth Association for Surveying and Land Economy (CASLE) United Kingdom, 2002)
Precise height determination using a single GPS receiver is now possible, following the establishment of GPS networks that include active stations with typical separations of about 100km. A method is described to determine precise heights when using a single GPS receiver and active stations of the National GPS Network of Great Britain.From the computation of the heights of 188 GPS stations distributed across the British mainland, a precision of 1.5cm was attained. This was achieved using only 4 hours of dual frequency static GPS data, but with scientific GPS processing software to mitigate systematic error effects.